Medical Treatment of Chronic Venous Insufficiency - Antignani, Pier L.; Caliumi, Chiara (Vascular Disease Prevention (Discontinued), 2007)
Chronic venous insufficiency (CVI) of the lower extremities is a complicated disorder that affects the productivity and well-being of millions of people worldwide. Management requires careful differential diagnosis and a systematic long-term multidisciplinary care effort directed toward realistic goals within the context of the patient's lifestyle. Patients suffering from any class of the Clinical, Etiological, Anatomical, Pathophysiological (CEAP) classification of chronic venous disease (CVD) may be symptomatic (C0s-C6s). Leg heaviness, discomfort, itching, cramps, pain, paresthesia and oedema (C3) are the most frequent manifestations of CVD and a major reason for medical consultation. The standard treatments for venous disease of the lower limb include compression bandaging and stocking as well as surgical removal of varicose veins. Drugs for the venous system were initially called phlebotonics as they were believed to act on venous tone. They are still largely used in the symptomatic treatment of CVI and to make patients more comfortable. Phlebotropic drugs, in their modern form, are aimed at a wide range of processes. They are naturally occurring, seminatural or synthetic substances, some of them combining two or more active principles to improve the efficacy. Most of these belong to the flavonoid family (such as diosmine, esperidine, troxoerutine, oxoerutine, etc.) and others are capillary protecting substances as escine, centella asiatica, bilberry anthocyanosides. Flavonoid drugs have been widely used in the management of the symptom of venous disease for many years and have recently been studied in some detail to assess their effects on the microcirculation. Phlebotropic drugs are widely prescribed and marketed in Italy, France, Germany and other parts of Europe. Their mechanisms of action vary, but their main property is activation of venous and lymphatic return. The effects of phlebotropic drugs on physiological parameters such us venous tone, venous haemodynamics, capillary permeability and lymphatic drainage have been studied by many well-conducted randomized, double-blind clinical trials. In particular, phlebotropic drugs participate in the heamodynamic re-equilibrium of the microvascular system consisting in reducing capillary permeability by increasing its resistance with the consequent reduction of interstitial fluid. A series of drugs have been recently introduced for the treatment of severe CVI (CEAP 4/5/6), as co-adjuvants. They are antithrombotic drugs (sulodexide, heparan sulfate, defibrotide) and vasodilators (pentoxifyllin and prostaglandin E1) for their specific action on endothelial alterations and blow flow patterns, and on microthrombi and their oxygen barrier effect.
Keywords: medical therapy